Influence of Risk Perception and Destination Image Mediated by Satisfaction Towards Destination Loyalty in Tanjung Lesung Tourism - Adam Raihan Rianthomy; Tasya Zahwa Prayoga; Filda Rahmiati; Felix Goenadhi (International Journal of Applied Business and International Management, 2023)
COVID-19 is seen as a hazard to the tourist sector. Knowing visitors' views of pandemic risk can help develop an effective and efficient approach to increasing the volume of visits to Tanjung Lesung. This study investigates the link and impact of perceived risk (health and socio-psychological) and destination image (cognitive and affective images) on destination loyalty mediated by Tourist Satisfaction. This study used a quantitative methodology using non-probability purposive sampling to provide this analysis. The sample analyzed included people who visited Tanjung Lesung, and 150 respondents who fit these criteria were discovered. Using the SEM-PLS method, this investigation's significance level was 5%. The results indicate that perceived risk was found to influence satisfaction also destination loyalty; hence destination image was found not to have a significant influence. From here, tourist industry players and the government may collaborate to strengthen public communication methods to boost the industry's favorable image and overcome crisis.